Factors affecting primaquine combination treatment in Malaria patients in Selangor, Malaysia - Norliza Mat Ariffin; Farida Islahudin; Mohd Makmor-Bakry; Endang Kumolosasi; Mohd Hafizi A Hamid (Wolters Kluwer Medknow Publications, 2017)
Introduction: Primaquine is vital for the management of liver-stage Plasmodium vivax and Plasmodium ovale malaria. However, primaquine effectiveness is dependent on various factors and differs between populations. Therefore, this study was conducted to identify factors that affect the length of stay and relapse during primaquine combination treatment in malaria-infected patients in the local setting. Materials and Methods: A retrospective study on the use of primaquine combination among P. vivax and P. ovale infected patients in Selangor, Malaysia within a 5-year period from 2011 to 2015 was obtained from the National Malaria Case Registry, Malaysia. Data collected were patient characteristics (age, gender, nationality, glucose-6-phosphate dehydrogenase, pregnancy); disease characteristics (survival, past malaria infection, parasite type, presence of gametocyte, parasite count, week onset, severity, transmission type); and treatment characteristics (type of antimalarial, treatment completion). Outcome measures were length of stay and relapse during a 1-year follow-up. Results: A total of 635 patients were included in the study. Based on a multivariate logistic regression analysis, the significant predictors for length of stay were gender (P = 0.009) and indigenous transmission (P < 0.001). Male patients had a shorter length of stay than females by 0.868 days (P = 0.009), and indigenous transmission took 1.82 days more compared to nonindigenous transmission (P < 0.001). Predictors for relapse were indigenous transmission of malaria (P = 0.019), which was 15.83 times more likely to relapse than nonindigenous transmission (P < 0.01). Conclusions: This study reveals that the effectiveness of primaquine was clinically associated with gender and indigenous transmission. To that end, vigilant monitoring of primaquine use is required to reduce relapse and future transmission.